An Aggregated Energy Security Index of Russia, 1990-2015 - Ragulina, Yulia Vyacheslavovna; Bogoviz, Aleksei Valentinovich; Lobova, Svetlana Vladislavlevna; Alekseev, Alexander Nikolaevich (International Journal of Energy Economics and Policy, 2018)
The paper analyzes energy security performance made by the Russian Federation in 1990-2015 on the basis of an aggregated index that includes the total of four dimension, namely (a) energy “affordability” and (b) “availability”, (c) “energy and economic efficiency” and (d) “environmental stewardship.” Each energy dimension is operationalized with three indicators that allow to quantitatively measure energy security performance of Russia each five years since the year of 1990. The analysis gives the opportunity to measure the overall development of Russia's energy security over the last 25 years and track the progress made each five years in every dimension. Thus, the paper gives not only a general understanding of how the energy security of one of the largest oil and gas producers in the world was developing in 1990-2015, but also gives insights on how every aspect of its energy security was changing. The paper concludes that Russia worsened its energy security in 2015 by 3.2 points (if compared to 1990). There was a steady decline in Russia's energy security performance in the period of 1995-2010, with a modest growth in 1990-95 and 2010-15. The worst decrease in Russia's energy security was observed in 1995-2000, with an overall decline of 3.8 points. The most venerable dimension of Russia's energy security was the energy “affordability” dimension because of the constantly rising costs on energy resources. Also, Russia performed poorly in the “economic and energy efficiency” dimension, but it demonstrated a positive growth over 25 years under analysis in the energy “availability” and “environmental stewardship” dimensions. Keywords: Energy Security, Russia, Security of Supply JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.7209